Explanatory Analysis of Factors Influencing the Support for Sustainable Food Production and Distribution Systems: Results from a Rural Canadian Community - Sahand Ashtab; Robert Campbell (Sustainability, 2021)
Investigating the viability of alternative food networks (AFNs) is more important than before because of the disruptions in global supply chains and evolving resident composition in different regions. In this regard, this paper reports on findings of a project aimed at identifying factors influencing support for local, sustainable food production, and distribution systems. In the first phase, local residents and international students in Cape Breton, Canada, were surveyed prior to the onset of the coronavirus disease 2019 (COVID-19) pandemic to assess their attitudes and values relative to shopping at farmers markets and buying local. In the second phase, mid-pandemic, text mining of Twitter data was used to gauge sentiments related to these same activities. The results of our explanatory analysis suggest that the top two factors influencing decisions to buy local farm products were food attributes and supporting community economic development. In contrast to previous studies, we included an alternate sample group, namely, international students, and explored the relevance of the social aspect of buying local, e.g., meeting the farmer. Among our findings from the application of a logistics regression model to our survey data (N = 125) is the suggestion that the senior non-international student residents of the Cape Breton Island were more probable to be in the category of consumers whose perception of an authentic buy-local experience was limited to distribution channels that allowed for the social aspect of buying local, e.g., meeting the farmer.